Neurologic injury after spinopelvic dissociation: Incidence, outcome, and predictors. Issue 2 (February 2023) - Morris, Cade A.; Moo Young, Justin P.; Savakus, Jonathan C.; Obey, Mitchel R.; Pereira, Daniel E.; Hills, Jeffrey M.; McKane, Ava; Babcock, Sharon N.; Miller, Anna N.; Stephens, Byron F.; Mitchell, Phillip M.
Highlights: Evaluating incidence and outcome predictors for neurologic injury in spinopelvic dissociation. Increasing kyphosis is associated with incidence of neurologic injury. Complete recovery from neurologic injury occurs in over half of all patients, with radiculopathy being the most common long-term sequelae. Abstract: Background: Traumatic spinopelvic dissociation is a rare injury pattern resulting in discontinuity between the spine and bony pelvis. This injury is associated with a known risk of neurologic compromise which can impact the clinical outcome of these patients. We sought to determine incidence and characteristics of neurologic injury, outcomes following treatment, and predictive factors for neurologic recovery. Methods: We reviewed the clinical documentation and imaging of 270 patients with spinopelvic dissociation from three Level-1 trauma centers treated over a 20-year period. From this cohort, 137 patients fulfilled inclusion criteria with appropriate follow-up. Details surrounding patient presentation, incidence of neurologic injury, and outcome variables were collected for each injury. Neurologic injuries were categorized using the Gibbons criteria. Multivariate analysis was performed to assess for patient and injury factors predictive of neurologic injury and recovery. Results: The overall incidence of neurologic injury in spinopelvic dissociation injuries was 33% (45/137), with bowel and/or bladder dysfunction (n=16) being the most common presentation. Complete neurologic recovery was seen in 26 cases (58%) and two patients (4%) improved at least one Gibbon stage in clinical follow-up. The most common long-term neurologic sequela at final follow-up was radiculopathy (n=12, 9%). Increased kyphosis was found to be associated with neurologic injury (p=0.002), while location of transverse limb and Roy-Camille type were not predictive of neurologic injury (p=0.31 and p=0.07, respectively). There were no factors found to be predictive of neurologic recovery in this cohort. Conclusion: Neurologic injury is commonly seen in patients with spinopelvic dissociation and complete neurologic recovery was seen in the majority of patients at final follow-up. When present, long term neurologic dysfunction is most commonly characterized by radiculopathy. While increasing kyphosis was shown to be associated with neurologic injury, no patient or injury factors were predictive of neurologic recovery.